2022
DOI: 10.3389/fonc.2022.998159
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indocyanine green fluorescence imaging-guided lymphadenectomy in radical gastrectomy for gastric cancer: A systematic review and meta-analysis

Abstract: BackgroundIndocyanine green (ICG) imaging-guided lymphadenectomy has been introduced in gastric cancer (GC) surgery and its clinical value remains controversial. The aim of this study is to evaluate the efficacy of ICG fluorescence imaging-guided lymphadenectomy in radical gastrectomy for GC.MethodsStudies comparing lymphadenectomy in radical gastrectomy between use and non-use of ICG fluorescence imaging up to July 2022 were systematically searched from PubMed, Web of Science, Embase and Cochrane Library. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…The median number of additional nodes that were retrieved after NIR visualization was approximately 1, resulting in an increase of only 2.3% in the total number of nodes retrieved. This result is in contrast with the previously cited meta-analysis (mean 7.4 additional LNs with ICG guidance) 16 and with the two available, randomized, controlled trials that respectively reported a mean number of 8.5 and 7.9 additional LNs. 12 , 17 As said before, this difference can be partially explained by the fact that in our study fluorescence was used only at the end of lymphadenectomy, when the procedure had already been judged as adequate by the operating surgeon.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The median number of additional nodes that were retrieved after NIR visualization was approximately 1, resulting in an increase of only 2.3% in the total number of nodes retrieved. This result is in contrast with the previously cited meta-analysis (mean 7.4 additional LNs with ICG guidance) 16 and with the two available, randomized, controlled trials that respectively reported a mean number of 8.5 and 7.9 additional LNs. 12 , 17 As said before, this difference can be partially explained by the fact that in our study fluorescence was used only at the end of lymphadenectomy, when the procedure had already been judged as adequate by the operating surgeon.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies, and a recent meta-analysis, suggest that fluorescence guided LND allows for a higher number of LNs harvested with respect to standard LND, possibly reducing intraoperative blood loss and without impact on operative time and postoperative complications. 16 Most of these studies (mainly comparative retrospective, only two randomized trials) compare ICG-guided LND to standard LND; allocation to either group is clearly not blinded, and the reasons for a better performance of ICG-guided LND in terms of number of retrieved LNs might be related to different factors that are not necessarily related to the effectiveness of fluorescence guidance. In this study, to overcome this potential bias, LND was performed as per local standards and NIR visualization was used after specimen extraction, in order to appreciate its crude effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual clinical value of ICG remains a matter of debate due to the current lack of confirmation from clinical studies. Additional high-quality randomized controlled tests to substantiate such benefits are urgently required ( 54 ). Although several studies have shown a markedly larger average count of lymph nodes detected for an ICG group than for a non-ICG group ( 55 ), some scholars reported the opposite result.…”
Section: Discussionmentioning
confidence: 99%